Underground pipeline corrosion : detection, analysis and prevention - Orazem, Mark E. (Woodhead Publishing series in metals and surface engineering ;, 2014)
This book provides a basic understanding of the problems associated with corrosion detection and mitigation, and of the state of the art in corrosion prevention. Topics include: basic principles for corrosion in underground pipelines; AC-induced corrosion of underground pipelines; significance of corrosion in onshore oil and gas pipelines; numerical simulations for cathodic protection of pipelines; use of corrosion inhibitors in managing corrosion in underground pipelines; magnetic flux leakage; close interval potential surveys (CIS/CIPS); Pearson surveys; in-line inspection; and use of both electrochemical and optical probes. While the emphasis is on pipelines transporting fossil fuels, the concepts apply as well to metallic pipes for delivery of water and other liquids. --